KEBIJAKAN HUKUM PIDANA DALAM UPAYA PENEGAKAN HUKUM LINGKUNGAN HIDUP - SoWoong Kim (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Law Number 32 Year 2009 on Environmental Protection and Management ( UUPPLH ) that have entered criminal provisions in Chapter XV , which consists of 23 chapters. Provision of punishment is much more complete and detailed than the Law Number 23 Year 1997 on the old Environmental Law, but still a lot of things that need to be addressed in the UUPPLH. The results showed that the enforcement of the criminal law to an act of formal law has a special event, because it relates to the principle ultimum, meaning that the effective use of criminal law to an act of formal law enforcement have to wait until the administration declared is no longer effective. To avoid difficulties in the enforcement of environmental law, the legislation specifically about formal law should be drafted clearly, firmly, not interpretations. Authors attempt to compare with Environmental Law in South Korea, in order to find a refinement of Law Number 32 of 2009. Key words: criminal law policy, enforcement of environmental law